A (in)efetividade da tutela coletiva na proteção de dados pessoais - Iszlaji, Bárbara de Oliveira (2023)
From the second half of the NOth century, society underwent an information and communications technology revolution, which deeply changed the socioeconomic context. Since the last decades, new technologies have been developed in such a way that economic activities are subordinated to the massive processing of information focused on the predictability of behavioral patterns of individuals or groups. In this context, the development of big data analytics technologies and profiling practices could result in violations of privacy and data protection not only to individuals but also to entire groups. Noticing such an environment triggered discussions about overcoming the individualistic nature of personal data protection. qis research aims to demonstrate how the Brazilian legal system, based on its General Personal Data Protection Law and the collective protection system, contributes to the effectiveness of collective protection regarding personal data. To reach its objective, the investigation is based on a bibliographic and documental review, as well as on the analysis of Brazilian and foreign legislation